Effects of roads on the vertebrates diversity of the Indigenous Territory Paresi and its surrounding - Brum,T. R. (2018)
Abstract Roadkill impact is still underestimated due to the lack of knowledge of its intensity and effect on animal populations. To assess differences between animal roadkills on roads in distinct landscapes, this study recorded meso- and megavertebrate roadkills along 50 km during a year in two highways in the transitional area of Amazonia/Cerrado in Tangará da Serra, Mato Grosso: MT-358 and MT-235, the latter crossing the Paresi Indigenous Land. We assessed roadkill rates and points with higher rates of roadkills, recording the most impacted species, seasonal effects, biomass loss, activity period of species, and traffic volume. We recorded 178 roadkills in 4,950 km travelled, a rate of 0.035 animal/km-travelled. Mammals were the most impacted with 135 roadkills (75.8%), followed by reptiles (6.2%), amphibians (5.6%) and birds (5.1%). Among mammals 51.1% were Carnivora, and the most impacted species was Cerdocyon thous (n = 42). On highway MT-358 (human-modified landscape), we recorded 155 roadkilled mammals, and the most impacted were C. thous (23.9%) and Euphractus sexcinctus (13.5%). Whilst on highway MT-235 (Paresi Indigenous Land), we recorded 23 roadkilled mammals, and the most impacted were Myrmecophaga tridactyla (26.1%) and C. thous (21.7%). The low roadkill rate in the Paresi Indigenous Land might be related to the presence of fauna pathways along the highway and the availability of a forested landscape.